A Study on Factors Associated With Spread of Covid 19 among Health Care Delivery Workers in Jabalpur District [India] - Toppo, Neelam Anupama; Soni, Deepali; Dubey, Priyanka; Mishra, Priyank (International Journal of Innovative Research in Medical Science, 2020)
Introduction: COVID-19 is an infectious disease caused by the most recently discovered coronavirus. This new virus and disease were unknown before the outbreak began in Wuhan, China, in December 2019. One target during this pandemic is to control infection by promoting the use of Masks, hand sanitizations and maintaining the social distance. And the key spreaders as well most vulnerable for Covid-19 are Medical care staff (Doctors, Nurses, paramedical workers, ward boy etc). Objectives: To assess what factors were responsible for spread the disease and to understand the pattern of spread of COVID-19 among these workers. Methodology: An exploratory study design conducted among the COVID-19 positive Doctors, Nurses, and paramedical staff working in Govt. or private set up. Through Telephonic conversation, data was collected. Result: 75% of a positive health professional was from NSCB medical college which has been designated as COVID Health Centre. The staffs are providing Critical care to Covid patients, Anaesthetics, Surgeons, Nurses, ward boys are at high risk for acquiring the disease. Out of 40 positive cases, only two had history of travel. Even people who wore PPE were also got infected. Maximum 38% were those who were wearing a mask but not all the time gloves. 20% were those who neither wearing masks nor gloves during exposure with contacts. Among those who were symptomatic most of them had fever followed by Fever with cough and cold, Fever with weaknesses and coughing, sore throat, body ache, etc. Conclusion: efforts are needed to reduce lapses in compliance with masking, use of gloves or the practice of hand hygiene and maintaining the social distancing in non-patient care areas, wards and OPDs.